2022
DOI: 10.3389/fsurg.2022.883935
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 pandemic on Vascular Surgery Unit activity in Central Romania

Abstract: The COVID-19 outbreak has placed substantial pressure on the medical systems worldwide. This study aimed to investigate the influence of the prepandemic vs. pandemic period on the activity of the Vascular Surgery Unit of a large emergency hospital in Eastern Europe. We performed a retrospective review of the vascular surgery cases admitted, comparing the statistics from the two time periods. We examined data of a total of 1,693 patients over the two periods. We report a 34.51% decrease in the surgical procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 34 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…From December 2019 until now (16 October 2022), the Coronavirus disease (COVID-19) has affected over 629 million people and caused 6,571,064 deaths worldwide, having a negative impact on the medical practice [ 1 , 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…From December 2019 until now (16 October 2022), the Coronavirus disease (COVID-19) has affected over 629 million people and caused 6,571,064 deaths worldwide, having a negative impact on the medical practice [ 1 , 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) declared a global pandemic on March 2020, in response to the sudden outbreak the COVID-19, which spread quickly from China across the world [ 1 ] and had a very negative impact on the medical activity [ 2 ]. Experience from previous pandemics has shown that exposure to the SARS virus results in feeling fear and guilt about exposing families to infection loneliness, anxiety, and depression [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other side, an adverse development of cardiac emergency care has been reported with inexplicable low numbers, i.e., of myocardial infarction, during phases of high COVID-19 incidence [ 25 ]. Further articles show that this development does not only apply to medicine but also to emergency and elective surgery of all kinds [ 4 , 5 , 26 , 27 ]. Di Martino et al provide an interesting study that connects the fields of oncology with surgery by assessing the variations in elective oncological surgery on colorectal and breast cancer during the first pandemic year of 2020 in comparison to the previous years of 2018 and 2019.…”
Section: Discussionmentioning
confidence: 99%